INVOLVEMENT OF YOUTH IN MARRIAGE RELATED DECISION MAKING IN INDIA - Bhakat, Priya (European Scientific Journal, ESJ, 2015)
In India marriage are typically family arranged in which parents are mostly involved in selection of potential spouses for their children. This paper tries to focus on the role and level of involvement of youth in spouse selection. Above 90 percent of the marriages are arranged in India and except for the southern states, majority of married young men and women meet their spouse on the wedding day. Women seems to be more worried and anxious about getting married as in contrast majority of the men are excited about getting married although there is hardly any interaction among couples prior to marriage, especially in Bihar, Rajasthan and Jharkhand. Odd ratios reveals that mothers education have a significant and positive relationship on the respondent’s opinion regarding choice of marriage partner. However, unlike the mother’s education, religion, caste and work status does not show any association with the respondent choice of partner. Respondents who often discuss their personal issues with their parents tend to select their marriage partner themselves or they have a strong opinion in spouse selection.